Progesterone, Myo-Inositol, Dopamine and Prolactin Present in Follicular Fluid Have Differential Effects on Sperm Motility Subpopulations - Shannen Keyser (MDPI AG, 2021)
Considering the challenges surrounding causative factors in male infertility, rather than relying on standard semen analysis, the assessment of sperm subpopulations and functional characteristics essential for fertilization is paramount. Furthermore, the diagnostic value of sperm interactions with biological components in the female reproductive tract may improve our understanding of subfertility and provide applications in assisted reproductive techniques. We investigated the response of two sperm motility subpopulations (mimicking the functionality of potentially fertile and sub-fertile semen samples) to biological substances present in the female reproductive tract. Donor semen was separated via double density gradient centrifugation, isolated into high (HM) and low motile (LM) sperm subpopulations and incubated in human tubal fluid (HTF), capacitating HTF, HD-C medium, progesterone, myo-inositol, dopamine and prolactin. Treated subpopulations were evaluated for vitality, motility percentages and kinematic parameters, hyperactivation, positive reactive oxygen species (ROS), intact mitochondrial membrane potential (MMP) and acrosome reaction (AR). While all media had a significantly positive effect on the LM subpopulation, dopamine appeared to significantly improve both subpopulations’ functional characteristics. HD-C, progesterone and myo-inositol resulted in increased motility, kinematic and hyperactivation parameters, whereas prolactin and myo-inositol improved the LM subpopulations’ MMP intactness and reduced ROS. Furthermore, progesterone, myo-inositol and dopamine improved the HM subpopulations’ motility parameters and AR. Our results suggest that treatment of sub-fertile semen samples with biological substances present in follicular fluid might assist the development of new strategies for IVF treatment.